2015
DOI: 10.7897/2277-4343.06253
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pilonidal Sinus With Ayurvedic Ksharasutra Therapy: A Case Study

Abstract: Pilonidal sinus is chronic condition consisting of a midline pit situated in midgluteal cleft at postanal region usually associated with hairs. Prolong sitting, presence of deep natal cleft, obesity, repeated irritation due to hair, family history may increase the risk of disease. In Ayurvedic science acharya Sushruta mentioned eight types of sinuses as nadivrana. Among these pilonidal sinus can be considered under shalyaj nadivrana (sinus due to foreign body). Ksharasutra is a kind of thread coated with caust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It frequently gets infected due to desquamated epithelial debris in those who lack of proper hygiene. [11]…”
Section: Discussionmentioning
confidence: 99%
“…It frequently gets infected due to desquamated epithelial debris in those who lack of proper hygiene. [11]…”
Section: Discussionmentioning
confidence: 99%
“…Soni and Dahiya [77] reported 13 mm zone of inhibition when diethyl ether extract of P. karka was used against S. aureus. In this study, an aqueous extract of methylcellulose and polyvinyl alcohol composite showed antibacterial activity, indicating that the cellulose extraction process resulted in the extraction of some bioactive compounds along with cellulosic material.…”
Section: Evaluation Of Methylcellulose and Polyvinyl Alcohol Compositementioning
confidence: 99%